1995
DOI: 10.2174/092986730204220224094632
|View full text |Cite
|
Sign up to set email alerts
|

Anthracene-9,10-Diones and Aza Bioisosteres as Antitumor Agents

Abstract: Naturally occurring quinones which structurally consist of an anthracene-9,10-dione chromophore are important antitumor agents. The anthracycline antibiotics, in particular, doxorubicin, are major chemothera­ peutic agents. The pluramycins and the ene-diynes antibiotics also show pro­ i mise as antitumor drugs. The synthetic anthracene-9,10-diones such as mitoxantrone are potent antitumor agents. Analogues related to mitoxantrone have been synthesized and biologically evaluated. Aza and diaza bioiso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Many useful therapeutic drugs have their discoveries rooted in serendipity. In particular, one might note the development of the important anticancer drugs doxorubicin and mitoxantrone (Chart ). Mitoxantrone, an anthracene-9,10-dione, has gained an important position in the clinical management of leukemia and lymphomas as well as in combination therapy of advanced breast and ovarian cancers. Although mitoxantrone is endowed with an improved tolerance profile when compared with doxorubicin and other anthracyclines, it is not devoid of significant toxic side effects, especially those associated with myelosuppression and cardiotoxicity. , Mitoxantrone also shows a cross-resistance to cell histotypes developing resistance against doxorubicin mediated by overexpression of glycoprotein P. The cell-killing effects elicited by mitoxantrone are probably multimodal in nature . Several studies suggest that intercalation into DNA is a major cellular event and this intercalative interaction may serve as an anchor for the drug at specific base pair sites, , which is then followed by the critical cell-killing events.
1 Structures of Mitoxantrone and BBR 2778
…”
Section: Introductionmentioning
confidence: 99%
“…Many useful therapeutic drugs have their discoveries rooted in serendipity. In particular, one might note the development of the important anticancer drugs doxorubicin and mitoxantrone (Chart ). Mitoxantrone, an anthracene-9,10-dione, has gained an important position in the clinical management of leukemia and lymphomas as well as in combination therapy of advanced breast and ovarian cancers. Although mitoxantrone is endowed with an improved tolerance profile when compared with doxorubicin and other anthracyclines, it is not devoid of significant toxic side effects, especially those associated with myelosuppression and cardiotoxicity. , Mitoxantrone also shows a cross-resistance to cell histotypes developing resistance against doxorubicin mediated by overexpression of glycoprotein P. The cell-killing effects elicited by mitoxantrone are probably multimodal in nature . Several studies suggest that intercalation into DNA is a major cellular event and this intercalative interaction may serve as an anchor for the drug at specific base pair sites, , which is then followed by the critical cell-killing events.
1 Structures of Mitoxantrone and BBR 2778
…”
Section: Introductionmentioning
confidence: 99%
“…10,11 The anthracycline antitumor and antibiotic agents doxorubicin and daunorubicin (Figure 1) have been used for the treatment of several types of cancer such as breast and ovarian cancers, acute nonlymphocytic leukemia in adults, and acute lymphocytic leukemia in adults and children. 12 Anthracyclines intercalate between DNA bases, thus blocking DNA synthesis and transcription. They also inhibit the activity of topoisomerase II (Topo II), leading to breaks in genomic DNA.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Molecular modeling and molecular pharmacology studies of mitoxantrone and several structurally related compounds revealed that the mode of action of this drug is multimodal in nature, though it is considered to be an intercalating agent that exerts its action primarily through binding and interaction with DNA . A great deal of research effort has been directed toward the finding of some new derivatives that might retain the remarkable anticancer activity of this agent, while reducing or eliminating its side effects, mainly cardiotoxicity and the development of resistant tumors (MDR phenotype) . The intensive search for active compounds led to the in corporation of a pyrazole ring fusion at the 1- and 9-positions of the tricyclic skeleton of mitoxantrone.…”
Section: Introductionmentioning
confidence: 99%